Midazolam Orally for Sedation during Pediatric Intrathecal Chemotherapy: Unmet Need of Distress-Free Procedures for Cancer Kids in India - Mullapally, Sujith Kumar (Indian Journal of Medical and Paediatric Oncology, 2020)
Preprocedural sedation is the part of standard operating procedures for pediatric intrathecal chemotherapy in developed countries and uses predominantly intravenous route. In India, due to the limited availability of pediatric oncology facilities and the increased patient numbers at those centers, no such intervention is possible. This article discusses this issue and proposes the use of oral midazolam in this context for large-scale utilization.
Keywords: Intrathecal chemotherapy; midazolam; pediatric